Моделі мотивації персоналу на підприємствах енергетики - Костін, Д. Ю. (ХНУРЕ, 2017)
The place of subsystem of energy efficiency management for the machine building enterprises in the relationship of three subsystems: directly managing energy efficiency and subsystems internal and external changes was defined
Keywords: мотивація персоналу; енергетика; економічне моделювання